Down but Not Out: The Consequences of Pretangle Tau in the Locus Coeruleus - Termpanit Chalermpalanupap; David Weinshenker; Jacki M. Rorabaugh (Neural Plasticity)
Degeneration of locus coeruleus (LC) is an underappreciated hallmark of Alzheimer’s disease (AD). The LC is the main source of norepinephrine (NE) in the forebrain, and its degeneration is highly correlated with cognitive impairment and amyloid-beta (Aβ) and tangle pathology. Hyperphosphorylated tau in the LC is among the first detectable AD-like neuropathology in the brain, and while the LC/NE system impacts multiple aspects of AD (e.g., cognition, neuropathology, and neuroinflammation), the functional consequences of hyperphosphorylated tau accrual on LC neurons are not known. Recent evidence suggests that LC neurons accumulate aberrant tau species for decades before frank LC cell body degeneration occurs in AD, suggesting that a therapeutic window exists. In this review, we combine the literature on how pathogenic tau affects forebrain neurons with the known properties and degeneration patterns of LC neurons to synthesize hypotheses on hyperphosphorylated tau-induced dysfunction of LC neurons and the prion-like spread of pretangle tau from the LC to the forebrain. We also propose novel experiments using both in vitro and in vivo models to address the many questions surrounding the impact of hyperphosphorylated tau on LC neurons in AD and its role in disease progression.